Swiss Democracy - Linder, W. author. aut Link
XXIV, 246 p.
Keywords: An updated 3rd edition of this authoritative analysis of Swiss democracy, the institutions of federalism, and consensus democracy through political power sharing. Linder analyzes the scope and limits of citizens' participation in direct democracy, which distinguishes Switzerland from most parliamentary systems.